KOMBINASI SISTEM BERBASIS WEB DAN ANDROID SEBAGAI APLIKASI PRESENSI KEGIATAN MENGGUNAKAN QR CODE - Riovan Styx Roring; FX Nanang Sujatmiko (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2021)
Registration and list of attendees are an important factor to be done in formal and informal activities. The purpose is to know the attendees’ personal data and presence. Registration and presence using the manual method such as form filling in a piece of paper produce problem, among them is over excess of paper and time consuming presence activity. Therefore, a new efficient and effective system that take advantage of Android Smartphone and Quick Response Code (QR Code) as Smart Attendance System is needed. The use of Android and QR Code technology simplify registration and presence process so that the proses would be much faster and efficient. The design of QR Code presence application based on Android is using System Development Life Cycle (SDLC) Waterfall model and designed using Use Case Diagram and Entity Relationship Diagram. The presence application is made using combination of two platform, that is Android and web. On the Android Smartphone there are scanner and administrator profile. Whilst at the web platform contain participant, event, and admin database. The existence of the design and Smart Attendance system implementation, registration and list of attendees process will be faster, efficient, and used as on of the smart system to support the smart city is expected.